(3hUjI ajKGZhQSs - (3ajKGZhQKs
(3ChdgG (B:s
(3bGd Chd eG ChUjc Hg GdPjf dG jMd Hge GdehJ ef Gddg YR hLd s
(3BNQgG (B:s
(3MJi JUjQ eMdkG ai GdMb Jcf SGHMkG ai GdSYGOI ZjQ YGHO s
(3HgG fXGe GdJYbjHIs
Keywords: (3GdadSaI hGdefWbs